The Many in the One: Multiple Self States in Combined Psychotherapy. (June 2017) - Levin, Uri
According to some relational approaches, mental health is expressed by the ability to move between various self-states while maintaining the adequate presence of the illusion that the self is continuous in time and space. Patients undergoing combined therapy are granted with the inimitable space existing between the two forms of therapy—individual and group therapy. Within the combined therapy patients, as well as therapists, are challenged by the multiplicity of self-states arising in light of this complex situation as part of a mutual intersubjective process. The article analyses the advantages of the combined therapy in light of the theories dealing with multiple self states. A clinical vignette will be presented to illustrate the theoretical notions.